Automated segmentation and morphological characterization of placental intervillous space based on a single labeled image. (June 2023) - Rabbani, Arash; Babaei, Masoud; Gharib, Masoumeh
Abstract: In this study, a novel method of data augmentation has been presented for the segmentation of placental histological images when the labeled data are scarce. This method generates new realizations of the placenta intervillous morphology while maintaining the general textures and orientations. As a result, a diversified artificial dataset of images is generated that can be used for training deep learning segmentation models. We have observed that on average the presented method of data augmentation led to a 42% decrease in the binary cross-entropy loss of the validation dataset compared to the common approach in the literature. Additionally, the morphology of the intervillous space is studied under the effect of the proposed image reconstruction technique, and the diversity of the artificially generated population is quantified. We have demonstrated that the proposed method results in a more accurate morphological characterization of the placental intervillous space with an average feature relative error of 6.5%, which is significantly lower than the 11.5% error observed with conventional augmentation techniques. Due to the high resemblance of the generated images to the real ones, applications of the proposed method may not be limited to placental histological images, and it is recommended that other types of tissue be investigated in future studies. Graphical Abstract: ga1 Highlights: Example-based generation of placental histology microscopic images. Training a deep learning model for segmentation based on a single image with labels. Automated morphological characterization of inter-villous space to make bio-markers.